Case Report: Free-Floating Intracoronary Thrombus: Who Is the Convict? - Mantovani, Francesca; Paolini, Ambra; Barbieri, Andrea; Boriani, Giuseppe (Frontiers in Oncology, 2022)
In young patients, especially with no traditional coronary risk factors, hypercoagulable states may be always considered as alternative cause of acute coronary syndromes. The concomitant thrombotic and bleeding risk associated with myeloproliferative disorders complicates the decision making particularly regarding to long-term dual antiplatelet therapy. The chosen therapy may need to be frequently revisited, depending on the patient’s bleeding complications. We reported the case of a 49-year-old woman with acute myocardial infarction with no traditional risk factors for coronary artery disease where a myeloproliferative neoplasm was diagnosed.